Cultural interchange along the Indian Ocean during the global middle ages (700- 1500ad): the role of Arabs and Persians in Africa-China musical exchange - Ola, Adebola Mobolaji (College of Music, 2021)
The relationship between Africa and China remains one of the most important geopolitical and economic partnerships of the 20th and 21st centuries. The Africa-China relation, although relatively recent, has its foundation in previous relations dating back over 500 years ago. It is against this backdrop of longstanding relations that this research is situated as it aims to trace and examine Africa-China musical exchange between 700-1500AD. The main goal of this research is to answer the following questions: (1) Are there any musical exchange between Africa and China between 700 -1500AD? (2) If there are, what are these musical exchanges and how did they manifest? (3) Are these musical exchanges mutual? (4) If there are no musical exchanges during this period, why? (5) Are there any musical exchanges at any other time pre-700AD or post 1500AD? (6) What are some of the impacts of such a musical exchange? This research uses a historical framework in understanding and presenting Africa-China cultural relations. My hypothesis, given that Africa and China did not officially meet or establish formal relations until the early 15th century, posits that in the absence of direct musical exchange, the Arabs and Persians may have been the music brokers, circulating music both to Africa and China as they did with trade. Having consulted some translated primary sources, several secondary sources and iconographic materials obtained from libraries and archives, the research findings suggest that my hypothesis is partly correct. The Persians and specifically, the Arabs, were circulating musical and cultural practices around the Indian Ocean, all the way to Al-Andalusia (Arab Spain). This spread of music and culture, I argue, gave the region some musical uniformity within diversity. This uniformity is visible through the circulation of musical instruments such as the short-necked lute; the Persian barbat; the Arabian ūd; the Chinese pipa and the African kwitra, as well as the migration of musical ideas and musicians such as Barbad, Ziryab and Kang, throughout Asia, Africa and Europe. The direct musical exchange between Africa and China only takes place in the 20th century.